Efficacy and Safety Comparison Between Lorazepam and Diazepam in Treating Convulsive Status Epilepticus in Children: An Evidence-Based Case Report - Muhammad Habiburrahman; Widya Khairunnisa Sarkowi (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Indonesia still recommends diazepam for epilepsy, but the International League Against Epilepsy increasingly favours lorazepam. Some reports indicate diazepam being less effective and causing side effects. This report presents a difficult-to-treat convulsive status epilepticus (CSE) case in a 10-month infant who received diazepam, questioning if intravenous/rectal lorazepam is a better initial therapy than diazepam for hospitalized children with CSE. Methods: Following the patient-intervention-comparison-outcome (PICO) formula, we searched for evidence in four journal databases (Pubmed, Proquest, EBSCOHost, and Cochrane). Studies meeting inclusion and exclusion criteria were appraised. Results: Through three systematic reviews and meta-analyses, our clinical query was addressed. One study revealed that rectal lorazepam was more effective in stopping seizures than rectal diazepam (RR 2.86). Meanwhile, two studies found that intravenous lorazepam exhibited similar efficacy in seizure cessation compared to intravenous diazepam (RR 1.04 and OR 1.03, respectively). Both drugs showed no significant difference in the time required to stop seizures or the necessity for additional doses or adjunctive medications to achieve such cessation, nor in the likelihood of refractory seizure within 24 hours. Two studies indicated that intravenous lorazepam had a reduced risk of respiratory depression (RR 0.71 and OR 0.62, respectively). Regardless of the administration route, lorazepam was linked to a lower probability of ICU admission (RR 0.15) than diazepam. Conclusion: Intravenous lorazepam and diazepam are equally effective for treating CSE, but rectal lorazepam is considered better at stopping seizures and preventing their recurrence compared to diazepam. Furthermore, lorazepam is deemed safer, especially when given intravenously.